Combining Hydrophilic and Hydrophobic Materials in 3D Printing for Fabricating Microfluidic Devices with Spatial Wettability (Adv. Mater. Technol. 9/2021). Issue 9 (12th September 2021) - Männel, Max J.; Weigel, Niclas; Hauck, Nicolas; Heida, Thomas; Thiele, Julian
Abstract : Photopolymer Formulations In article number 2100094, Julian Thiele and coworkers describe a set of newly developed hydrophilic and hydrophobic photopolymer formulations, processed by a sophisticated example of Digital Light Processing‐based 3D printing to fabricate microfluidic flow cells with planar channel geometries that exhibit spatially tailored wetting behavior. The applicability of these flow cells is exemplary shown for forming single emulsion droplets as well as oil‐in‐water‐in‐oil double emulsion droplets.